NILAI SYAIR SAYED IDRUS BIN SALIM ALJUFRI (GURU TUA) DAN IMPLIKASINYA PADA PENDIDIKAN KARAKTER - Jayadin, Ahmad; Lembah, Gazali; Karim, Ali (BAHASANTODEA, 2017)
This research aims to describe the value contained in the poem of Sayed Idrus bin Salim Aljufri and the implication of poem value of Sayed Idrus bin Salim Aljufri on character education. Type of research is qualitative research. The data used were qualitative from poem of Sayed Idrus bin Salim Aljufri. Technique of collecting data there are three that is, documentation, recording and interview. Data analysis techniques are descriptively inductive. The research results show that there were 11 values contained in the verse of Sayed Idrus bin Salim Aljufri namely the values of education, social, religious, philosophy, historical, psychological, economic, moral, legal, cultural, and struggle. The implications of poetry value in character education, among others, the value of education implies with self that includes motivation to study, love science, logical thinking, critical, creative and innovative. Social values have implications for self and sesame in the form of hard work, good manners and good speech. Religious values imply on the relationship with God Almighty in the form of thoughts, words and actions pursued based on the value of the Deity / religious teachings. The value of philosophy implies self-love of knowledge. Historical value implies the fellow and the environment that is appreciating the work and achievements of others; attitudes and role models prevent damage to the natural environment surrounding. The value of psychology has implications for itself in the form of responsible attitudes. The economic value implies itself as an entrepreneurial spirit. The moral values implicated in them are honest and polite. The value of the law has implications for the relationship with God Almighty and to others who obey the social rules. The culture value has the own implications in the form of hard work, courteous and appreciate the work of others. The value of struggle has implications of national and nationalist values.